(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the issue of teaching students’ stable basic English phrases for emergency situations, the problem of using innovative technologies in the formation of intercultural competence of students of higher educational institutions in the process of learning foreign languages. Particular attention is focused on the types of games that can be used in the process of language training for students. The intricacies of using theatrical activity as a type of art technology, its function in improving practical language acquisition and developing students’ communication skills are analyzed.